Trend of hand, foot and mouth disease before, during, and after China’s COVID control policies in Zhejiang, China - Ding, Zheyuan; Lu, Qinbao; Wu, Haocheng; Wu, Chen; Lin, Junfen; Wang, Xinyi; Fu, Tianying; Yang, Ke; Song, Queping (Frontiers in Public Health, 2024)
ObjectiveTo describe the trends in the incidence of hand, foot and mouth disease (HFMD) before, during, and after China’s Coronavirus Disease (COVID) control policies, and to interpret the influence on HFMD incidence at different control stages in Zhejiang Province.MethodsWe collected data on HFMD cases in Zhejiang between 2014 and 2023. We compared the constituent ratios of cases at different COVID control stages by sex, age, child groups, and pathogens and weekly seasonal indices to observe seasonal variations in the incidence of HFMD. An interrupted time-series segmented regression analysis was applied to estimate the influence on HFMD incidence at different control stages. Stratified and sensitivity analyses were conducted to validate the findings.ResultsA considerable proportion of cases occurred among children living separately. The proportions of children in kindergartens or nurseries and children aged 2–4 years were relatively low at the strict control stage compared to the other three stages. Enteroviruses other than enterovirus 71 and coxsackie virus A16 were the dominant HFMD pathogens, and the proportion showed an increasing trend. The usual spring–summer peak in HMFD incidence did not occur in 2020, and the periodicity of the biennial peak was disrupted for a year. The summer peak in 2023 was higher than that in the other years, and was delayed by 3 weeks. The trend changes in weekly HFMD cases during the strict control and regular control stages were − 15% (IRR: 0.85, 95% CI: 0.81–0.89) and 17% (IRR: 1.17, 95% CI: 1.12–1.23), respectively. However, the change was not statistically significant during the reopening stage (IRR: 1.41, 95% CI: 0.34–5.88). The expected number of cases increased by 1.12 times (95% CI: 243.17, 53.45%) during the reopening stage compared to what would have occurred if the zero-COVID policy had continued in 2023.ConclusionNon-pharmaceutical interventions (NPIs) for COVID-19 control can mitigate HFMD. However, after the dynamic zero-COVID policy ended, the HFMD incidence returned to historical levels. Strict NPIs such as traffic restrictions and kindergarten closures cannot be sustained long-term. NPIs such as improving personal hygiene for routine prevention are highly recommended.